Implementasi NodeMCU sebagai Sistem Deteksi Dini Bahaya Banjir di Purwodadi Berbasis Web dengan Notifikasi Bot Telegram - Wijaya Ariyanto, Pradipta Andre; Soelistijadi, R (Universitas Merdeka Malang, 2022)
Purwodadi Town is one of the areas of Central Java, every time it rains some places will be flooded. And the heavy and long-lasting rainfall resulted in flooding. Floods cause losses for affected communities and damage existing infrastructure. One solution is to make an early warning system for flood disasters, the researchers designed a device based on the nodemcu microcontroller and used telegram as a notification. The researcher applies the prototype method to analyze all the needs starting from the input, output and interface description, then do the design. The results of this study are an early flood hazard detection system with telegram notifications that can be accessed through a website with various features, namely real-time water level information, graphical water level reports, and additional users to get notifications. The prototype produced from this research, the public can know whether a flood occurs or not so that they can anticipate before the flood occurs